PENGARUH ATRIBUT BUDAYA ORGANISASI TERHADAP KEPERCAYAAN ORGANISASI DAN KINERJA KARYAWAN DI HOTEL INNA GARUDA YOGYAKARTA - Teguh Suripto (Universitas Alma Ata, 2013)
Abstract This study will analyze the subject matter Is there a positive influence between organizational characteristics , organizational leadership , organizational commitment , employee management, success criteria partially on Organizational Trust , Is there a positive influence between organizational characteristics , organizational leadership , organizational commitment , management employee , partial success criteria partially employee performance , Is there a positive influence between organizational characteristics , organizational leadership , organizational commitment , employee management, with the same success criteria of the Trust organization , Is there a positive influence between organizational characteristics , organizational leadership , organizational commitment , employee management, with the same success criteria partially employee performance. The analysis used is regression analysis on two stages , the first stage is to test the independent variable on the dependent variable Organizational Trust , and the second phase to test the independent variables through organizational confidence variables to variable employee performance . After analysis of test results obtained by the first stage of the five independent variables are organizational Character , Leadership , Organizational Commitment , Employee Management , and success criteria , the dependent variable organizational trust , which has a significant effect only two variables: organizational commitment , and success criteria . While in the second stage of testing , the independent variables were tested through the organization of trust on employee performance result that only the commitment of the organization, which has significant influence over the organization of trust on employee performance. From the results of the test conducted discussion , that the variable attributes of organizational culture that directly affect or significantly affect the confidence of the organization, only organizational commitment and success criteria . While the attributes of organizational culture that has significant influence through trust organization to employee performance , organizational commitment only . For the organization of trust significantly affect the performance of employees Keywords : Attributes of Organizational Culture , Faith Organizations , Employee Performance